Time-Varying Effects of External Shocks on Macroeconomic Fluctuations in Peru - (:unkn) unknown (Springer Nature Switzerland, 2024)
This study uses a family of VAR models with time-varying parameters and stochastic volatility (TVP-VAR-SV) to analyze the impact of external shocks on output growth and inflation in Peru in 1992Q1-2017Q1. The statistical relevance of the models is assess...
Keywords: Macroeconomía; Perú